Effect of the acid hydrolysis conditions on the functional properties of microcrystalline cellulose II (2012)
ABSTRACT: Microcrystalline cellulose II (MCCII) was prepared from wood cotton. Hydrolysis conditions were performed according to the Box Benhken design composed of three factors: acid type (hydrochloric, sulfuric and nitric acids), acid concentration (1, 3 and 5 M) and reaction time (3, 4 and 5 h). Hydrolysis conditions only affected particle size, flow rate, degree of polymerization and dissolution rate of spironolactone. However, only the effect of hydrolysis on particle size and flow rate was considered as significant. The quadratic model determined hydrolysis with 2.2 M HCl or H2SO4 for 3h and as the optimal reaction conditions to produce a MCCII with a particle size of ~100 μm and flow rate of ~20 g/sec. The validation runs gave particle size and flow rate values of 112 μm and 24.3 g/sec and 96 μm and 17.2 g/sec when hydrochloric and sulfuric acids were employed, respectively. Further, compacts made of MCCII and spironolactone (a poorly soluble drug) released at least 80% of the drug between 18-34 min, independent of the hydrolysis conditions employed.